Water Quality Status of the Pangkajene River: A STORET-Based Assessment - Nasrul Nasrul; Erman Syarif; Abdul Malik; Ramli Umar; Hasriyanti Hasriyanti (Universitas Negeri Gorontalo, 2026)
This study assessed the water quality status of the Pangkajene River using the STORET method based on physical, chemical, and biological parameters. The research employed a quantitative descriptive-evaluative approach using 11 water quality parameters measured at 12 sampling points representing the upstream, middle, and downstream sections of the river. The observed parameters were compared with Class II water quality standards established under Government Regulation No. 22 of 2021. Water quality status was determined using the STORET scoring system to identify pollution levels and dominant parameters contributing to water quality degradation. The results showed that the Pangkajene River was classified as lightly to moderately polluted, with STORET scores ranging from −8 to −20. No sampling points were categorized as having good water quality or heavy pollution. Chemical Oxygen Demand (COD) was the main parameter exceeding the quality standard across all sampling points, followed by Total Suspended Solids (TSS), turbidity, Biological Oxygen Demand (BOD), and Escherichia coli. In contrast, pH, Dissolved Oxygen (DO), nitrate, phosphate, and Total Dissolved Solids (TDS) generally remained within acceptable limits. Higher pollution levels were observed in the middle and downstream sections of the river, indicating the influence of human activities along the watershed. These findings highlight the need for improved watershed management and pollution control measures to support sustainable water resource management and contribute to the achievement of SDG 6 related to water quality improvement.